International Financial Statistics Country Notes 2013. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2013)
This issue of International Financial Statistics (IFS), Country Notes presents, in two sections, brief information on the data published in IFS. The first section provides a description of the compilation techniques underlying selected area and world tables. The second identifies for each country the standard sources of the statistics and provides some explanatory material on each country's data, including any breaks in the series. Country Notes is designed to be a companion volume to each version of IFS: the monthly print edition, the yearbook, the CD-ROM, and the Internet. It will normally appear as an annual volume and will be shipped with the print edition of the International Financial Statistics Yearbook during August each year. The aggregate Industrial Production Index for the industrial countries as a group is calculated by the Statistics Department from industrial and manufacturing production indices that are published in the country pages. Private commercial banks report data based on the Gregorian calendar, while state-owned commercial banks report data based on the Solar calendar. This results in differences in the interbank positions for other depository corporations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet